Duta Merek dan Citra Merek terhadap Keputusan Pembelian - Afiril Inisia Hajar; Toni Herlambang; Jekti Rahayu (BUDGETING : Journal of Business, Management and Accounting, 2022)
This study aims to determine and analyze the influence of brand ambassador and brand image on purchasing decisions of Mi Sedaap Korean Spicy Chicken products in the KPOPERS Jember community. The research method uses this type of research with a quantitative approach, namely research on certain populations and samples. The population in this study were 116 active members of the Jember KPOPERS Community, with a sample of 54 respondents or 10% of the total population obtained by purposive sampling method which was calculated based on the slovin formula slovin formula. The data collection technique used a questionnaire with Likert scale measurements. The data analysis technique used is descriptive analysis, data instrument test, classical assumption test, and the final hypothesis test with the help of SPSS version 26. The results show, a) the results of the t-test regression analysis on the brand ambassador variable (X1) have a significant effect on purchasing decisions. (Y); b) the results of the t-test regression analysis on the Brand image variable (X2) have a significant effect on purchasing decisions (Y); c) the results of the regression analysis of the coefficient of determination show that the brand ambassador variable and brand image as a whole have an effect on purchasing decisions by 48%, while the remaining 52% is explained by other variables not discussed in this study. In conclusion, Mi Sedaap brand ambassador Choi Siwon has a positive and significant effect on product purchasing decisions, and brand image has a positive and significant impact on purchasing decisions for Mi Sedaap Korean Spicy Chicken products in the Jember KPOPERS community. The independent variables of the study, namely brand ambassadors and brand image as a whole have an effect on purchasing decisions by 48% based on the R² value. Keywords: Brand Ambassador, Brand image, Purchase Decision